(untitled) (Journal of the College of Basic Education, 2022)
The text of the poet Abd al-Nabi al-Shayea is full of structural, semantic and phonetic manifestations, which allows the researcher to embark on the world of rhetorical and stylistic analysis due to its diversity and its multiple capabilities for analysis. The poet’s sense of feelings of disappointment and helplessness in front of the authoritarian regime in Iraq in the seventies and the beginning of the eighties until the nineties.